(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article evaluates the frequency of TORCH infections among women of reproductive age in the Samarkand region. Although no targeted epidemiological study was conducted to estimate regional prevalence, the work analyzes screening data obtained during routine laboratory testing. The results primarily reflect the serological immune response to the pathogens that form the TORCH group. The purpose of the study was to examine laboratory findings associated with TORCH markers using ELISA.